Optimizing expert and patient input in pediatric trial design - Dhaenens, Britt A.E. (2023)
Funding Information: The conect4children (c4c) project has received funding from the Innovative Medicines Initiative 2 Joint Undertaking under grant agreement no. 777389. The Joint Undertaking receives support from the European Union's Horizon 2020 Research and Innovation Program and EFPIA. The publication reflects the authors' views and neither IMI nor the European Union, EFPIA, or any Associated Partners are responsible for any use that may be made of the information contained therein. EU‐PEARL has received funding from the Innovative Medicines Initiative 2 Joint Undertaking under grant agreement no. 853966. This Joint Undertaking receives support from the European Union's Horizon 2020 research and innovation program and EFPIA and Children's Tumor Foundation, Global Alliance for TB Drug Development Non‐profit Organization, and Springworks Therapeutics Inc. This publication reflects the authors' views. Neither the IMI nor the European Union, EFPIA, or any Associated Partners are responsible for any use that may be made of the information contained herein. M.S. was supported in part by the Robert Bosch Stiftung, Stuttgart, Germany. Publisher Copyright: © 2023 The Authors. Clinical and Translational Science published by Wiley Periodicals LLC on behalf of American Society for Clinical Pharmacology and Therapeutics.